DINAMIKA PENGAMBILAN KEPUTUSAN PENJUAL JAMU TRADISIONAL DALAM MEMBERIKAN LAYANAN ABORSI - , Untung Eko Setyasari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Abortion is prohibited and stipulated in KUHP as a form of criminal act. However, no matter how severe communityâs blasphemy on abortion, there are still many women experiencing unwanted pregnancy are looking for abortion service. The situation is worsened by the fact that those women are facing difficulties in accessing medically safe abortion service. The gap is then turned into business opportunities by traditional herbalists who provide abortion service. Decision of traditional herbalists to provide abortion service is very interesting to be studied. The aims of the research are to examine the process of decision making of traditional herbalists to provide abortion service and the reason they decide to do it. The study used qualitative approach by case study method. It was perceived to be the right method since the characteristic of study case method was to answer the questions âHow?â and âWhy?â concerning certain phenomenon studied. The subjects of the research are seven traditional herbalists and five crosscheck informants. The result of the research finds that the traditional herbalists will think first before they act when they respond the abortion request. Their thinking process is manifested in the process of decision making to give or not the abortion service. For the process, the subjects use the approach of decision making by the social learning process and communication with their significant person. From that way, they can improve the choice alternatives and then think about all of the consequences from each alternative. The subjects are inclined to make decision without vanish the risk through secretly marketing strategy and selective to choose the prospective patients. The result of the research also explains the process of decision making from various perspectives, starting from legal, economic, morality and social. Besides the result of the research also shows that abortion service giving is a choice that they choose freely. That choice is not separated from the motivation to fulfill their basic needs, namely the need of survival, belonging & loving, power, freedom and fun.